Salmonella enterica Serovar Enteritidis Enterocolitis during Late Stages of Gestation Induces an Adverse Pregnancy Outcome in the Murine Model - Noto Llana, Mariangeles (2014)
Foodborne diseases caused by Salmonella enterica serovar Enteritidis (S. Enteritidis) are a significant health problem. Pregnancy, state of immunological tolerance, is a predisposing condition for the development of infections with intracellular pathogens. Salmonella species can cause pregnancy complications such as chorioamnionitis, transplacental fetal infection, pre term labor, abortions, neonatal and maternal septicemia. However, the specific mechanisms by which Salmonella infections trigger these alterations are not clear. In the present work, using a self-limiting enterocolitis murine model, we show that the ingestion of a low dose of S. Enteritidis at late stages of pregnancy (day 15 of gestation) is sufficient to induce massive maternal infection. We found that Salmonella infection leads to 40% of pre term delivery, 33% of abortion and fetal growth restriction. Placental dysfunction during S. Enteritidis enterocolitis was confirmed through cellular infiltration and hypoxia markers (MPO activity and COX-1 and COX-2 expression, respectively). Apoptosis in placental tissue due to Salmonella infection was also evident at day 18 of gestation when investigated by morphometric procedure, DNA fragmentation and Fas/FasL expression. Also, the expression of IFN-γ, TNF-α, IL-17 and IL-10 was up regulated in response to Salmonella not only in placenta, but also in amniotic fluid and maternal serum. Altogether, our results demonstrate that S. Enteritidis enterocolitis during late stages of gestation causes detrimental effect on pregnancy outcome.